Mindfulness-Based Attention Training: Feasibility and Preliminary Outcomes of a Digital Course for High School Students - Alissa J. Mrazek; Michael D. Mrazek; Jordan V. Reese; Arianna C. Kirk; Lefeba J. Gougis; Alex M. Delegard; David J. Cynman; Casey M. Cherolini; Peter C. Carr; Jonathan W. Schooler (MDPI AG, 2019)
Digital mindfulness-based interventions (d-MBIs) present an unprecedented opportunity to share mindfulness training at scale. However, the feasibility of digital mindfulness training for high schools remains unknown. Using a one-group pre−post design, this feasibility study evaluated the adoption of a digital mindfulness course in a public high school. The 22-day course was delivered on laptops, tablets, or phones via a custom digital learning platform. The course included a total of 2.25 h of instruction designed to improve focus, stress management, and emotion regulation. The intervention was implemented across 11 classrooms with 9th−12th grade students. On average across all classes, students completed 80% of lessons and 77% of daily exercises. Although the one-group design precludes definitive conclusions about the intervention’s effects, paired t-tests from pretest to post-test (N = 190) revealed improved emotional regulation and stress management despite students experiencing significantly increased life demands toward the end of the academic term. Results suggest that students also adopted a stronger growth mindset about their ability to focus, and they felt more motivated and confident to train this ability. A total of 64% of students indicated that the course improved their focus. Among the 81.6% of students who reported at baseline that they paid attention in class less than they should, focus during class increased significantly. This investigation supports the feasibility of digital mindfulness training for high schools and highlights strategies for increasing fidelity of implementation of digital interventions in school settings.